Implementation of Differentiated Learning Process Based on Students' Initial Mathematics Ability - Fanzeka, Danial; Subakti, Sultoni Sukri; Anugrah, Fandy; Mustafa, Sriyanti (Proceeding International Conference on Mathematics and Learning Research, 2023)
This study was motivated by the low learning outcomes of students in learning mathematics caused by the diverse characters of students, especially in the aspect of students' initial mathematical abilities. This study aims to improve students' learning outcomes in learning mathematics by using process differentiation based on students' initial abilities. The method used in this research is classroom action research (CAR). The research procedure followed the Kemmis & Taggart model, namely planning, action, observation, and reflection which was carried out in 2 cycles. The research subjects were students of class VIII.1 SMP Negeri 29 Bulukumba totaling 21 people, students of class VIII.1 SMP Negeri 10 Parepare totaling 32 people and students of class VIII.5 SMP Negeri 1 Mattiro Bulu totaling 26 people. The collection technique in this study was done through a learning outcome test. The results of research using process differentiation based on the initial ability of students showed an increase in learning outcomes. Based on the results of the research obtained the results of the actions provided, namely in cycle I students experienced an increase in learning outcomes compared to pre-cycle learning outcomes. However, because it has not met the standard of success, namely classical completeness reaching 85% of the students present, the provision of action is continued in cycle II. Then in cycle II students again experienced an increase in learning outcomes from cycle I and had achieved completeness of more than 85% of the students present. Based on the results of the research and discussion, it can be concluded that the application of differentiated learning process based on the initial mathematics ability of students carried out in the even semester of the 2022/2023 school year in three different schools located in South Sulawesi, namely SMP Negeri 29 Bulukumba (subject A), SMP Negeri 10 Parepare (subject B) and SMP Negeri 1 Mattiro Bulu (subject C) can improve students' mathematics learning outcomes.